Festschrift to honor F. Wilbur Gingrich lexicographer, scholar, teacher and committed Christain layman - Barth, Eugene Howard; Cocroft, Ronald Edwin (Leiden Brill, 1972)
Includes bibliographical references.
Keywords: Gingrich, Felix Wilbur, -- 1901-; Bible -- criticism, interpretation, etc